Antecedents of Employee Intention to Leave the SMEs - Mudrifah Mudrifah; Dian Rokhmawati (Faculty of Economics, State University of Jakarta., 2019)
The purpose of this study was to find out how the effect of the antecedents of intention to leave involve job dissatisfaction and work-related stress in the Small Medium Entreprises (SMEs). The variables were moderated by the perceived alternative job opportunities (PAJO) as Indonesian Migrant Workers. A total of 89 questionnaires were distributed to the employees of SMEs located in Ngunut District, Tulungagung Regency, East Java, Indonesia. The Data were analyzed using the associative descriptive method, using PLS version 3.0 software. The results of the analysis obtained in this study indicate that work dissatisfaction and work-related stress have a positive influence on the intention to leave the SMEs. The perceived of alternative job opportunities as Indonesian migrant workers successfully moderating the effect of employee work-related stress on the intention to leave SMEs in Ngunut District, Tulungagung Regency.